2016
DOI: 10.1016/j.pcl.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis

Abstract: THE EARLIEST DESCRIPTIONS OF LUNG DISEASE IN PEOPLE WITH CYSTIC FIBROSIS (CF) DEMONSTRATED THE INVOLVEMENT OF THREE INTERACTING PATHOPHYSIOLOGICAL ELEMENTS IN CF AIRWAYS: MUCUS OBSTRUCTION, INFLAMMATION, AND INFECTION. OVER THE PAST 7 DECADES, OUR UNDERSTANDING OF CF RESPIRATORY MICROBIOLOGY AND INFLAMMATION HAS EVOLVED WITH THE INTRODUCTION OF NEW TREATMENTS, WITH INCREASED LONGEVITY, AND WITH INCREASINGLY SOPHISTICATED LABORATORY TECHNIQUES. IN THIS CHAPTER, WE WILL REVIEW THE CURRENT STATE OF UNDERSTANDING … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 106 publications
1
19
0
2
Order By: Relevance
“…Therefore, vitamin D deficiency, common in CF patients due to malabsorption, can influence immune response, and has been associated with inflammatory markers, bacterial infection, and pulmonary exacerbation …”
Section: Introductionsupporting
confidence: 71%
“…Therefore, vitamin D deficiency, common in CF patients due to malabsorption, can influence immune response, and has been associated with inflammatory markers, bacterial infection, and pulmonary exacerbation …”
Section: Introductionsupporting
confidence: 71%
“…Progressive airways disease due to persistent and recurrent bacterial infection is the primary cause of morbidity and mortality in patients with cystic fibrosis (CF) (Ratjen et al, 2015). Accordingly, many studies have investigated infection dynamics and identified associations between infections with several specific organisms and a poor prognosis (Zemanick and Hoffman, 2016). Not surprisingly, the focus of many such studies has been on "classical" CF pathogens -prevalent organisms such as Pseudomonas aeruginosa, Staphylococcus aureus, and the Burkholderia cepacia complex.…”
Section: Introductionmentioning
confidence: 99%
“…Important organisms related to chronic pulmonary infections in CF patients are Staphylococcus aureus and Pseudomonas aeruginosa (5,6). They can persist for a long time, i.e., 6 to 70 months, in the CF lung and thereby adapt to their specific environ-ment (7,8).…”
mentioning
confidence: 99%